Controlling Singlet–Triplet Energy Splitting for Deep‐Blue Thermally Activated Delayed Fluorescence Emitters. (30th December 2016) - Cui, Lin‐Song; Nomura, Hiroko; Geng, Yan; Kim, Jong Uk; Nakanotani, Hajime; Adachi, Chihaya
Abstract: The development of efficient metal‐free organic emitters with thermally activated delayed fluorescence (TADF) properties for deep‐blue emission is still challenging. A new family of deep‐blue TADF emitters based on a donor–acceptor architecture has been developed. The electronic interaction between donor and acceptor plays a key role in the TADF mechanism. Deep‐blue OLEDs fabricated with these TADF emitters achieved high external quantum efficiencies over 19.2 % with CIE coordinates of (0.148, 0.098).